Reflection of Wind Turbine Noise from Rough Ground Using 3D Multiple Scattering Theory - James Naylor; Qin Qin (Wind, 2025)
Ground roughness is investigated for its influence on the propagation of wind turbine noise by using a proposed multiple scattering theory to predict the reflection of sound waves from a deterministic distribution of hemispheres. By using a distribution of hemispheres as an approximation for a realistic rough ground, a semi-analytical formulation for the reflected sound pressure is possible. Experiments are conducted within the University of Hull’s anechoic chamber and the results are compared against predictions from the proposed theory. Good agreement between the results is shown. The proposed multiple scattering theory also gives results consistent with a three-dimensional boundary element method, while having significantly shorter computation times and smaller memory requirements. Furthermore, results remain accurate up to the point where the radii of the hemispheres are comparable to the wavelengths of interest, which means that the scattering effect can be investigated more completely. When the proposed theory was applied to the unique source–receiver geometry of a wind turbine and a human height receiver, the excess attenuation calculated over an array of receivers showed significant fluctuations in sound pressure which were attributed to the ground roughness. Further works aim to incorporate weak refraction effects and ground absorption to analyze the relative influence of different parameters.